Lithium-induced nephrogenic diabetes insipidus following improved medication compliance: a case report - Eugene Annor; Ishita Bhattacharya; Mary Bass; Emily M. Horvath (Journal of Medical Case Reports)
Abstract Background Nephrogenic diabetes insipidus is a rare, often underrecognized complication of long-term lithium therapy. Lithium-induced nephrogenic diabetes insipidus results from chronic renal exposure, leading to significant polyuria, dehydration, and hypernatremia. Case presentation We describe a case of a 55-year-old White caucasian male with a schizoaffective disorder managed with lithium who presented with altered mental status and electrolyte abnormalities following a recent stroke. Evaluation revealed nephrogenic diabetes insipidus as the primary etiology, likely exacerbated by recent changes in medication adherence. The patient responded well to fluid resuscitation, reduced lithium dosage, and targeted electrolyte management. Conclusion This case underscores the need for vigilance in monitoring patients with nephrogenic diabetes insipidus on chronic lithium therapy, as early recognition and treatment are essential in preventing renal impairment and improving clinical outcomes.